LUMBAR VERTEBRAE RADIOGRAPHY WITH SUSPECTED SPONDYLOSIS AT MEDAN ADVENTIST HOSPITAL - Helvinus Laia; Sri Nanda Sihotang (Journal of Public Health Science, 2025)
Lumbar Radiography with suspected Spondylosis is an examination to show anatomy and abnormalities in the lumbar spine using x-rays. Spondylosis is a term used to describe degenerative changes that occur in the articular components of the spine. Spondylosis can be said to be the development of osteophytes (bone spurs) along the joints of the vertebral body and intervertebral discs. The projections used are Antero-Posterior and Lateral x-ray planes used general x-ray unit using 200 mA. Image recording using Digital Radiography (DR) The type of research conducted is a qualitative and descriptive method. Data collection techniques using documentation and observation.